1986
DOI: 10.1038/bjc.1986.136
|View full text |Cite
|
Sign up to set email alerts
|

Importance of quantitative histology of bone changes in monoclonal gammopathy

Abstract: Quantitative histology of bone changes, using undecalcified transiliac bone biopsies (UTBB), was performed blindly in 46 individuals with monoclonal gammopathy (MG), including 17 with MG of undetermined significance (MGUS) and 29 with overt multiple myeloma (MM). Three MGUS presented an excess of osteoclastic resorption (OR) in the vicinity of clusters of tumour cells and developed overt B cell malignancies, chronic lymphocytic leukaemia, Waldenström's disease and MM respectively. On the other hand, MGUS with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 23 publications
2
28
0
2
Order By: Relevance
“…Until now, the studies have focused on the presence of an excessive bone resorption associated with a low bone formation in patients with advanced MM (4,5,14). Of importance, we have recently demonstrated that this uncoupling process was di- rectly responsible for the lytic bone lesions in myeloma patients (14 (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, the studies have focused on the presence of an excessive bone resorption associated with a low bone formation in patients with advanced MM (4,5,14). Of importance, we have recently demonstrated that this uncoupling process was di- rectly responsible for the lytic bone lesions in myeloma patients (14 (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative histology of bone changes was performed as previously described on undecalcified transiliac bone biopsy specimens (5,14,15). BONE …”
Section: Bone Histomorphometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the degree of bone involvement in MM and in monoclonal gammopathies of undetermined significance (MGUS, plasma cell dyscrasias which evolve into malignant lymphoplasmocytic diseases in approximately one third of cases (Bladé and Kyle, 1995) could be important for clinical guidance (Bataille et al, 1986), but is limited by the invasiveness of the presently available standard method, the quantitative bone histology. This problem has been partly overcome by the quantification of biochemical markers of bone turnover, such as osteocalcin as a marker of bone formation (Bataille et al, 1990) and the degradation products of type I collagen as indexes of bone resorption (Elomaa et al, 1992;Pecherstorfer et al, 1997).…”
mentioning
confidence: 99%
“…This imbalance is particularly evident in patients with advanced MBD and illustrated by histomorphometric studies showing the extreme paucity of newly formed bone near osteolytic lesions [9]. Patients with multiple bone lesions also display a reduction in their serum levels of bone-formation markers, such as alkaline phosphatase, osteocalcin, and procollagen type-I propeptides, coupled with a moderate to severe increase in markers of bone resorption, including ionized calcium levels [10].…”
Section: Introductionmentioning
confidence: 99%